HEPATITIS C VIRUS INFECTJON IN RENAL TRANSPLANTATION - Oya ÖVÜNÇ; Fundu TÜRKMEN; İzzet TİTİZ and A. Remzi DALAY and Kemal Nuri ÖZERKAN and Cihan ERSAN and Güler YAYLI (Turkish Journal of Gastroenterology, 2020)
-